Penerapan Prinsip Akuntabilitas Dan Transparansi Dalam Pelayanan Publik Pada Kantor Camat Marisa - Umuri, Hasman (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2019)
Principles of accountability and transparency essentially intended to assess the performance of a government, accountability and transparency is the basis for measuring the success of the performance of the government, but many people’s perception that the government considers that today many are not accountable, and aims to obtain transparan. Penelitian a description of the application of the principles of accountability and transparency in public services at the district office districts marisa marisa pohuwato. This study uses qualitative research methods with the number of informants as many as ten people. Data were collected through interviews and document study. The results showed that public participation is still low with an indication of the willingness of society and arrogance are still high for participating, the competence of the district office personnel are lacking in the task that is given in result of a lack of training on basic tasks and functions of each apparatus. It is suggested to all parties involved, especially the community to begin to change the paradigm that does not understand the fundamental importance of the activities held by local authorities, and then to the associated apparatus are suggested to the leadership in order to program the training activities regarding the duties and functions of each field.